Altered Th17/Treg balance and therapeutic targeting of RORγ in primary focal hyperhidrosis - Lin, Min; Lin, Jianbo; Du, Quan; Tu, Yuanrong; Chen, Jianfeng (Frontiers in Immunology, 2025)
BackgroundPrimary focal hyperhidrosis (PFH) significantly impacts patients’ physical and mental health, yet its underlying mechanisms remain unclear.MethodsThis study involved 80 healthy controls and 60 patients each with primary palmar (PPH), craniofacial (PCH), or axillary hyperhidrosis (PAH). Peripheral blood mononuclear cells (PBMCs) were analyzed via flow cytometry to assess Th17 and Treg cell populations. Cytokine levels were measured in patient serum using ELISA, while sweat gland tissue from PAH patients underwent gene expression analysis. A pilocarpine-induced mouse model of hyperhidrosis was used to test SR2211, a RORγ inverse agonist.ResultsPFH patients exhibited a disrupted Th17/Treg balance, with increased Th17 and decreased Treg cells across all subtypes compared to controls. Elevated IL-17 and IL-6 and reduced IL-10 and TGF-β1 levels were observed in PFH serum. Sweat glands showed increased RORγt and decreased FOXP3 expression. In mice, SR2211 treatment reduced sweat secretion, secretory granules, and serum acetylcholine. It also lowered Th17 infiltration, serum IL-17/IL-6, and IL-17A expression in sweat glands.DiscussionPFH is associated with a Th17/Treg immune imbalance. SR2211 alleviated hyperhidrosis and Th17-related inflammation in mice, highlighting the potential of targeting the RORγ–Th17 axis as a therapeutic strategy for PFH.